Metode Spread Spectrum untuk Penyisipan Pesan pada Citra Digital - Herri Setiawan; Bedy Briliant Wijaya; Dewi Sartika (Bulletin of Computer Science Research, 2023)
Abstract The importance of the value of information in a message means that the message often does not reach the recipient, but instead falls into the hands of unwanted people. Various techniques are used to prevent access by unauthorized persons. One of the various techniques to protect this information is steganography, which is the hiding of a message inside another message to avoid suspicion that someone is trying to steal information. The initial stage of the insertion process is to perform a binary spread of the message characters with a scalar magnitude of 4 to produce a new segment followed by the generation of a random number (pseudonoise random number) using the steganography key and converted into binary form. Then proceed with modulation with XOR logic operation between the value of the binary segment and the line of random numbers that have been converted into binary to produce a new binary that will be inserted into the digital image object. The spread spectrum method produces quite good image quality after the insertion process, this can be proven by the PSNR test results which are more than 30 dB.